Missing Items in Zakat Distribution: A Case in Kelantan, Malaysia - Ahmad Fahme Mohd Ali; Mohd Faisol Ibrahim; Muhammad Ridhwan Ab Aziz (International Journal of Zakat, 2019)
This study attempts to analyze missing items in current zakat distribution among the poor and needy zakat recipients in Kelantan. The study is motivated by few shortcomings of current zakat distribution as well as an increasing amount of expenditure annually on the two categories of zakat recipients, and yet the number of poor (fuqara) and needy (masakin) households is increasing. The current amount of zakat monthly distribution seems to raise some issues due to its weaknesses. This paper examines several missing elements in the current zakat distribution in Kelantan, Malaysia. The research was conducted through in-depth interviews with selected zakat recipients from a variety of socio-economic-cultural backgrounds in Kelantan, Malaysia. This study recommends that these items should be included in future zakat distribution in order to improve and strengthen the Muslims economy condition, and then, it would facilitate the poverty alleviation programs by the zakat department. Keywords: Zakat Poverty Line, Had Kifayah, Poor and Needy, Kelantan, Malaysia